Effects of FGF2 on characteristics of ovine mammary epithelial cells and milk production traits in dairy sheep - Zhao, Yuan; Li, Mingna; Hao, Zhiyun; Che, Longjie; Ren, Chunyan; Wang, Jiqing; Xu, Rui; Hu, Haixiong; Li, Mingjie; Li, Yijuan; Feng, Yuxin; Wang, Zike (Frontiers in Veterinary Science, 2026)
IntroductionFibroblast growth factor 2 (FGF2), a pleiotropic growth factor, promotes the elongation of mammary ducts and therefore contributes to the morphological development of mammary. It plays a crucial role in the development of mammary gland and lactation processes. However, the impact of FGF2 on milk production traits in sheep remains unexplored.MethodsIn the study, the effects of FGF2 on the characteristics of ovine mammary epithelial cells (OMECs) were investigated. Meanwhile, penta-primer amplification refractory mutation system (PARMS) was used to look for single nucleotide polymorphisms (SNPs) in nine regions of ovine FGF2. Additionally, the associations of sequence variations in FGF2 with variations in average daily milk yield and seven milk composition traits were also investigated in 449 Yuansheng Aite dairy sheep.ResultsAmong seven ovine tissues expressed by FGF2, it had the highest expression levels in liver and mammary gland tissue. Over-expressed of ovine FGF2 increased the viability, proliferation number and ratio of OMECs, as well as triglyceride content of OMECs. Conversely, silencing of ovine FGF2 produced the opposite effect to over-expression. A total of four novel SNPs were identified, with three located in intron 1 and one in intron 2. The genotypes and presence (or absence) of alleles from FGF2 were found to affect milk production traits in sheep. Ewes with the genotype AA at c.282 + 11,288 G/A had higher milk protein percentage, milk fat percentage, dry matter content and ash content. The presence of allele G at the c.282 + 11,288 G/A locus were associated with milk production traits described above in sheep.DiscussionThese findings indicate that FGF2 may serve as a potential molecular marker for improving milk production traits in sheep.